Trends and determinants of perinatal mortality in Bangladesh - Hossain, Md. Belal; Mistry, Sabuj Kanti; Mohsin, Md; Rahaman Khan, Md Hasinur (PLOS ONE, 2022)
This article was published in The Plos One [ © 2019 Hossain et al. This is an open access article distributed under the terms of the Creative Commons Attribution License] and the definite version is available at: https://doi.org/10.1371/journal.pone.0221503. The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0221503